Water Quality Improvement Using Floating Treatment Wetland for Sustainable Management of Dams and Reservoirs - Asmaliza M.N.N.; Mohd Sidek L. (Springer, 2023)
The development of dams and reservoirs in Malaysia are very much dependent on its water resources for diverse human activities such as agriculture, industries, settlements, hydro-electric power and any human needs. The development of dams can be associated with the number of effects including the changes to hydrology, water quality and river morphology. Therefore, the concerted efforts need be carried out to reduce these pollutants thus comply with the Interim National Water Quality Standard. The water quality improvement method using the Floating Treatment Wetlands has been introduced which provides a medium for vegetation that could absorb the nutrients. The objective of this paper is to identified performance of Floating Treatment Wetland as water quality improvement. The results for the selected water quality parameters such as Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), Total Nitrogen (TN), Total Phosphorus (TP), Magnesium (Mg) and Iron (Fe) indicated the removal efficiency was 97.62% for TSS, 91.3% for BOD, 36.36% for COD, 62.96% for TP, 70.28% for TN, 96.65% for Fe and 45.3% for Mg. The findings from this study indicate the contribution of Floating Treatment Wetlands as one of the methods to improve the quality of water. 2020, Springer Nature Singapore Pte Ltd.